Pengaruh Csr, Gcg, Pengungkapan Laporan Berkelanjutan, Risiko Perusahaan, Dan Kepemilikan Asing Terhadap Pengungkapan Sdgs - Novandito, Lucky; Trisnawati, Rina (SEIKO : Journal of Management & Business, 2024)
This study aims to determine the effect of CSR, GCG, Sustainability Report Disclosure, Corporate Risk, and Foreign Ownership on SDGs Disclosure. The theory used is the legitimacy and stakeholder theory with the target of the study being energy sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sample determination used a purposive sampling technique and resulted in 76 samples. Data analysis in this study used multiple regression analysis. The results of the study indicate that Sustainability Report Disclosure and Corporate Risk have an effect on SDGs Disclosure while CSR, GCG and Foreign Ownership have no effect on SDGs Disclosure.